SITANOS EFFECTIVENESS IN IMMIGRATION SERVICES IN THE NON-TPI TANGERANG CLASS I IMMIGRATION OFFICE - Muhammad Hilal Pratama (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
The launch of an innovation by the Immigration Office Class I Non-Border Control of Tangerang in the form of a web-based information technology system. This system is a simple system in bridging the immigration application submission process. Sitanos (Immigration TANgerang Online Service) was created to support better immigration services to the community, where this innovation is expected to make it easier for applicants to apply for immigration services by cutting their application flow. This study uses a quantitative method that aims to determine the effectiveness of using Sitanos in immigration services at the Immigration Office Class I Non-Border Control of Tangerang. Therefore the hypothesis of this research is that Sitanos is effectively used in the service of immigration documents for foreigners at the Immigration Office Class I Non-Border Control of Tangerang. The population of this study were employees of the Immigration Office Class I Non-Border Control of Tangerang. The research population is saturated in nature where all respondents are used as samples because the population is relatively small, amounting to 14 people. In determining the effectiveness of using Sitanos, using the system effectiveness test model from DeLone and McLean (2015). The results of the correlation coefficient analysis obtained a significance value of 0.000 and a correlation value of 0.956. In the simple linear regression test, it shows that the t value of the Sitanos variable is 11.297 with a significance of 0.000. Then it can be concluded that the research hypothesis (H1) is accepted and proven correct. So it can be proven that there is an influence between the use of Sitanos on immigration document services at the Immigration Office Clas I Non-Border Control of Tangerang and it can be stated that Sitanos is effectively used to support immigration document services for foreigners at the Immigration Office Class I Non-Border Control of Tangerang.